Faktor yang Mempengaruhi Kualitas Hidup Pasien Kanker yang Menjalani Kemoterapi - Nur Laila; Indah Sri Wahyuningsih; Mohammad Arifin Noor (Lembaga Pengembangan Kinerja Dosen, 2025)
Cancer is one of the leading causes of morbidity and mortality in Indonesia. Chemotherapy treatment often causes both physical and psychological side effects, which can reduce the patient's quality of life. Various factors, such as family support, economic status, education level, and knowledge, are suspected to influence the quality of life of cancer patients undergoing chemotherapy. This study aims to analyze the factors associated with the quality of life of cancer patients undergoing chemotherapy at Sultan Agung Islamic Hospital Semarang. This study used a non-experimental quantitative design with a correlational approach. Data were collected using questionnaires distributed to 84 respondents undergoing chemotherapy at the hospital. Bivariate analysis was performed using the Chi-Square test to examine the relationship between factors that are suspected to affect the quality of life of patients. The results showed that family support, economic status, education level, and knowledge level were significantly related to the quality of life of cancer patients. Specifically, the p-values obtained were 0.035 for family support, 0.000 for economic status, 0.036 for education level, and 0.049 for knowledge level. These findings indicate that social, economic, and educational factors play a crucial role in improving the quality of life of cancer patients undergoing chemotherapy. Therefore, special attention should be given to family support, knowledge enhancement, and better access to economic resources for cancer patients. As a result, their quality of life, especially during chemotherapy, can be improved. Keywords: quality of life, family support, economic status, education level, knowledge level.